Live-Action Role Playing for Safety Training: Effectiveness Evaluation in two Italian Companies. (August 2022) - Ricci, Federico; Bravo, Giulia
Researchers, corporate decision-makers, government agencies, and international bodies want to know how to improve safety and limit the serious social and economic consequences of occupational injuries. Understanding how to deliver effective training is important to achieving this aim. Gamification is considered a new frontier in effective safety training. This study tested the use of gamification in safety training, considering two Italian companies that used a live-action role-play methodology called "PratiCARE la Sicurezza." Workers who were required by Italian law to receive safety training or retraining participated in a pre–post study. Collection of measures relating to knowledge, attitudes, behaviors, and perception of the health and safety climate took place at baseline and immediately after the intervention. Participants' average safety knowledge at the end of the training was significantly better than the initial level, indicating that the training improved workers' knowledge level.